Comparison of Parameters for Programming Adjustable Dental Articulators by Using Wax Eccentric Records and Arcus Digma Device - Kristina Mage; Robert Ćelić; Samir Ćimić; Nikša Dulčić (University of Zagreb. School of Dental Medicine, 2019)
Objectives: Programming of joint mechanism/parameters (sagittal condylar inclination and Bennett angle) of adjustable dental articulators is a prerequisite for performing positions and movements of the mandible. The aim of the study was to test significant differences between the two methods (wax eccentric records and Arcus Digma device) of measuring these joint parameters by using three different dental articulators (SAM 3, Protar 7; and Artex CR). Materials and Methods: Thirty asymptomatic younger (age 25.7 ± 2.9 years) subjects (dental medicine students) divided by gender, with normal occlusion (Angle class I) participated in the study. After taking anatomical impressions of both dental arches, master casts were made of hard dental plaster for each subject. The values of the left and right sagittal condylar inclination and Bennett angle by the two methods of wax eccentric protrusive and lateral records and Arcus Digma device were measured for the purpose of programming the mentioned joint parameters in three different articulator systems. Results: The average values of the measured parameters of sagittal condylar inclination and Bennett angle of wax eccentric records were higher (ranging from 5ºto 10º) in relation to the values measured by Arcus Digma device. Statistically significant differences found between the measured joint parameters (p <0.025) were influenced by the articulator system design and measurement methods (t-test for dependent samples and MANOVA). Conclusion: The use of Arcus Digma device should be considered reliable and valid for individualized programming of dental articulators, rather than the use of wax eccentric records.